Integration of shared mobility approaches in Sustainable Urban Mobility Planning. Topic guide. - Arndt, Wulf-Holger; Drews, Fabian; Hertel, Martina; Langer, Victoria; Wiedenhöft, Emmily (My University, 2019)
Die Publikation basiert auf dem Konzept des "Sustainable Urban Mobility Planning" (SUMP) der Europäischen Kommission, welches die einzelnen Schritte einer nachhaltigen urbanen Mobilitätsplanung vorgibt. Der Fokus der Broschüre liegt dabei auf Sharing-Konzepten und ihren Einsatzmöglichkeiten in der kommunalen Verkehrsplanung.

This document provides guidance on a specific topic related to Sustainable Urban Mobility Planning (SUMP). It is based on the concept of SUMP, as outlined by the European Commission s Urban Mobility Package and described in detail in the European SUMP Guidelines (second edition). Numerous sharing concepts have emerged in recent years, which have been developing dynamically ever since. Some sharing concepts - esp. station-based car sharing - address alternatives to car ownership in order to reduce the space consumption, but others serve rather as an additional mobility option to get around: free floating car sharing and public bike rental systems, newer phenomena in the form of e-Scooter sharing and e-Moped sharing, on-demand mobility concepts (ride hailing and ride sharing) as well as the shared transport of goods (freight transport). The brochure concentrates in particular on sharing services and the starting points for municipalities within a SUMP. It shows the steps in sustainable urban mobility planning when particular planning aspects must be taken into account while integrating sharing modes.
Keywords: Kommunale Verkehrsplanung; Stadtverkehrsplanung; Verkehrsentwicklungsplan; Verkehrsträger; Verkehrsangebot; Modal Split; Elektromobilität; Gemeinschaftsnutzung; Mobilitätskonzept; Geschäftsmodell; Shared Mobility; Sustainable Urban Mobility Plan (SUMP); Geteilte Mobilität